2010
DOI: 10.5194/bg-7-3915-2010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ocean acidification on marine fish sperm (Baltic cod: <i>Gadus morhua</i>)

Abstract: Abstract.Ocean acidification, as a consequence of increasing marine pCO 2 , may have severe effects on the physiology of marine organisms. However, experimental studies remain scarce, in particular concerning fish. While adults will most likely remain relatively unaffected by changes in seawater pH, early life-history stages are potentially more sensitive -particularly the critical stage of fertilization, in which sperm motility plays a central role. In this study, the effects of ocean acidification (decrease … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…In other species, such as Pacific white sea bass ( Atractoscion nobilis ), larval fish otolith development in response to elevated CO 2 conditions showed an increased otolith size (area) compared with controls, although it was not determined whether these changes affected orientation and behaviour of young fish, or their survival (Checkley et al , ). Similarly, Frommel et al () found no deleterious effects of realistic changes in pH on the motility of sperm in Atlantic cod ( Gadus morhua ) in the Baltic Sea. By contrast, Ishimatsu et al (personal communication) found that high CO 2 and warm temperature together resulted in high larval mortality in the clownfish Amphiprion ocellaris and in the medaka ( Oryzias javanicus ).…”
Section: Factors Affecting Responses To Climate Change: Physiologicalmentioning
confidence: 88%
“…In other species, such as Pacific white sea bass ( Atractoscion nobilis ), larval fish otolith development in response to elevated CO 2 conditions showed an increased otolith size (area) compared with controls, although it was not determined whether these changes affected orientation and behaviour of young fish, or their survival (Checkley et al , ). Similarly, Frommel et al () found no deleterious effects of realistic changes in pH on the motility of sperm in Atlantic cod ( Gadus morhua ) in the Baltic Sea. By contrast, Ishimatsu et al (personal communication) found that high CO 2 and warm temperature together resulted in high larval mortality in the clownfish Amphiprion ocellaris and in the medaka ( Oryzias javanicus ).…”
Section: Factors Affecting Responses To Climate Change: Physiologicalmentioning
confidence: 88%
“…Sperm velocity was either not affected by environmental variation, such as increased temperature and decreased water pH in several marine invertebrates (Byrne et al 2010), the Atlantic cod (Frommel et al 2010), or the oyster (Havenhand & Schlegel 2009), or that environmental variation affected males differently in such a way that consistent population variation did not emerge.…”
Section: Sperm Function May Determine Species Rangesmentioning
confidence: 99%
“…Using offspring from a population of cod from the Baltic Sea-a region of relatively low Ω arag -Frommel et al (2010-Frommel et al ( , 2013 found either no or very modest effects on cod sperm, embryos, and young larvae. Working with off spring from a population of cod from the Norwegian coast, however, Frommel et al (2012) and Maneja et al (2013a,b) found a variety of negative effects on older larvae, highlighting the possible importance of differences in population source, duration of exposure, and developmental stages inspected to the observed response.…”
Section: Oca Effects On Finfishmentioning
confidence: 99%